REPEATED COVID-19 INFECTION EXISTS: A CASE SERIES FROM PAKISTAN - Zia Ul Haq; Fazid, Sheraz; Yasar Mehmood Yousafzai; Mohammad Noor; Arsalan Khan Ibrahimzai; Arif Iqbal; Naeem Ullah; Akhtar Sherin (Journal of Ayub Medical College Abbottabad, 2021)
Background: Protection against SARS-CoV-2 in infected individuals of COVID-19 is lacking. We report a case series of repeated infections of SARS-CoV-2. Methods: A total of 12 patients were identified with repeated infections for SARS-CoV-2 from 25 April 2020 to 16 March 2021 from Pakistan. Repeated infection was defined as diagnosis of the SARS-CoV-2 with real-time reverse transcriptase-polymerase chain reaction (RT-PCR) tests in the first and second phase of infection after complete recovery from the first phase of infection with a negative RT-PCR. Results: Of the 12 participants, 75% (n=9) were male and mean age of the participants were 40.1±9.7 years. Mean duration between the first and second phase of infection was 184±68.9 days. Patients presenting with mild infection in the first phase largely developed moderate to severe infection in the second phase. None of them were vaccinated. Conclusion: The pandemic of COVID-19 is on the rise and repeated infection from SARS-CoV-2 is occurring.